Comparison of plant microbiota in diseased and healthy rice reveals methylobacteria as health signatures with biocontrol capabilities - Oeum, Kakada; Suong, Malyna; Uon, Kimsrong; Jobert, Léa; Bellafiore, Stéphane; Comte, Aurore; Thomas, Emilie; Kuok, Fidero; Moulin, Lionel (Frontiers in Plant Science, 2024)
Introduction Rice (Oryza sativa) is a staple food worldwide, but its production is under constant pressure from both abiotic and biotic stresses, resulting in high use of agrochemicals. The plant microbiome harbours microorganisms that can benefit plant health and provide alternatives to the use of agrochemicals. The composition of plant microbiomes depends on many factors (soil composition, age, and health) and is considered a primary driver of future plant health. To identify plant microbiomes that protect against disease, we hypothesised that asymptomatic rice plants in fields under high pathogen pressure (i.e., healthy islands of plants among predominantly diseased plants) might harbour a microbiota that protects them from disease. Material and Methods We sampled healthy and leaf-diseased plants in rice fields with high disease incidence in Cambodia and profiled their microbiota at leaf, root, and rhizosphere levels using 16S V3V4 and 18S V4 amplicon barcoding sequencing. Results Comparison of amplicon sequence variants (ASV) of the microbiota of healthy and diseased samples revealed both disease and healthy signatures (significant enrichment or depletion at ASV/species/genus level) in both fields. The genera Methylobacterium and Methylorubrum were identified health taxa signatures with several species significantly enriched in healthy leaf samples (Methylobacterium indicum, Methylobacterium komagatae, Methylobacterium aerolatum, and Methylorubrum rhodinum). A cultivation approach on rice samples led to the isolation of bacterial strains of these two genera, which were further tested as bioinoculants on rice leaves under controlled conditions, showing for some of them a significant reduction (up to 77%) in symptoms induced by Xanthomonas oryzae pv. oryzae infection. Discussion We validated the hypothesis that healthy plants in fields under high disease occurrence can host specific microbiota with biocontrol capacities. This strategy could help identify new microbes with biocontrol potential for sustainable rice production.